A Systematic Literature Review of Talent Management And Knowledge Management In Improving Higher Education Performance - Ramaditya, Muhammad; Maarif , Mohamad Syamsul; Affandi , M. Joko; Sukmawati, Anggraini (International Journal of Indonesian Business Review, 2022)
Purpose – This paper seeks to reveals talent management as a distinctive organizational strategy mechanism that affects knowledge management, university transformation, and the intellectual environment in high-performance education Methodology/approach – There were 753 articles total since only those that were ready for publishing and were written in English were chosen. A search of some of these publications with the keywords "talent management," "succession planning," "knowledge management," or "higher education" turned up 386 results. To make sure there were no duplicates included, we reviewed and double-checked the titles, abstracts, and problems from these papers, including literature review articles and meta-analyses. The total number of articles in the SLR findings was 73 articles to do a systematic literature review. Findings – It was found that. Talent development was identified as a potential link that transmits the effects of knowledge management on the organizational performance of private universities over time. To achieve this goal, employee development that is built on management knowledge within universities becomes an obligation in providing sustainable organizational performance. Novelty/value – This systematic literature review study adds to the body of evidence on the potential for originality in talent and knowledge management in higher education, particularly in terms of raising academic performance. The outcomes of talent management and talent reviews in order to prepare talent management from the perspective of providing an individual picture of each aspect higher education performance.